enyuluhan Pemanfaatan Tanaman Obat Keluarga (TOGA) Untuk Pencegahan Dan Penanggulangan Penyakit Hipertensi Desa Mareje Kecamatan Lembar Kabupaten Lombok Barat - Utami, Rafika; Widiastuti, Tri Cahyani; Purwanti, Ery (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The community service program on the use of TOGA family medicinal plants for the prevention and control of hypertension has been implemented in Mareje Village, Sheet District, West Lombok Regency. The purpose of this community service is to provide education about the benefits of family medicinal plants (TOGA) for first aid for mild health disorders and provide education about traditional medicines that have the potential to treat and prevent hypertension. Method This research was conducted quantitatively with the design of the Quasy Experiment method, namely by using a one group pre-post test design approach where in the experimental group a pre-test was carried out on the behavior of the extension before being given the material. Based on the analysis test, the Shapiro Wilk rank test resulted in a Sig value = 0.187 > 0.05 and the paired T test resulted in a Sig = 0.000 value for the knowledge level variable. Then it can be concluded